2019
DOI: 10.1007/s10212-019-00446-4
|View full text |Cite
|
Sign up to set email alerts
|

Measuring differentiated instruction in The Netherlands and South Korea: factor structure equivalence, correlates, and complexity level

Abstract: Differentiated instruction is considered to be an important teaching quality domain to address the needs of individual students in daily classroom practices. However, little is known about whether differentiated instruction is empirically distinguishable from other teaching quality domains in different national contexts. Additionally, little is known about how the complex skill of differentiated instruction compares with other teaching quality domains across national contexts. To gain empirical insight in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 64 publications
4
64
0
1
Order By: Relevance
“…Second, the Graded Response Model (GRM), an extended IRT model for ordered polytomous observed variables, was applied to understand the response behaviours and how the set of items performed (Samejima 1968;Perner and Imiya 2005). The MTQ items were visualised using R package 'psychotree' to explore the unidimensionality assumption further (Maulana et al 2015a(Maulana et al , 2019van der Lans et al 2019). The total information estimated by this model indicated the presence of a nonnormal distribution with the highest frequency towards the maximum scores (3-4) in the data (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the Graded Response Model (GRM), an extended IRT model for ordered polytomous observed variables, was applied to understand the response behaviours and how the set of items performed (Samejima 1968;Perner and Imiya 2005). The MTQ items were visualised using R package 'psychotree' to explore the unidimensionality assumption further (Maulana et al 2015a(Maulana et al , 2019van der Lans et al 2019). The total information estimated by this model indicated the presence of a nonnormal distribution with the highest frequency towards the maximum scores (3-4) in the data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…"My teacher teaches me to check my solutions", α = 0.85). Prior studies have shown that the items of the MTQ (Maulana et al 2016c;van de Grift et al 2014b) can be ordered in a unidimensional structure (Maulana et al 2015a(Maulana et al , 2019van der Lans et al 2019) and is valid and reliable across countries (Maulana et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The probability of a teacher to implement differentiation within classrooms increases when other teaching behavior domains are demonstrably better. Differentiation is related to other domains in a stage-like manner in which differentiated instruction is one of the demanding domains of teaching behaviors that is typically seen in the lessons of highly effective teachers who incorporate behaviors from other domains in their lessons too (Pietsch, 2010;Maulana et al, 2019). Teachers with relatively high teaching quality, are more likely to teach in a student-centered manner and take into account student differences into their teaching (Pietsch, 2010).…”
Section: Differences In Perceived Teaching Behavior Across Countriesmentioning
confidence: 99%